2012
DOI: 10.1155/2012/607584
|View full text |Cite
|
Sign up to set email alerts
|

Ethnopharmacokinetic- and Activity-Guided Isolation of a New Antidepressive Compound from Fructus Aurantii Found in the Traditional Chinese Medicine Chaihu-Shugan-San: A New Approach and Its Application

Abstract: Aims. We aimed to identify an antidepressive compound found in traditional Chinese medicine (TCM) by a new approach called ethnopharmacokinetic- and activity-guided isolation (EAGI). Methods. The new approach targets an unknown chromatographic peak produced by an absorbed compound found in oral Chaihu-Shugan-San (CSS) taken by patients with depression. Once the compound was isolated from Fructus Aurantii (FA), spectral data was employed to identify the compound. The effects of this compound, FA, and CSS on dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Currently, pharmaceutical research and development are very challenging because of high cost, high risk and lengthy research period (Fan et al, 2012). Traditional Chinese medicine (TCM) has attracted much attention owing to its effectiveness against many diseases and proven safety in clinical use over 8000 years (Xie and Leung, 2009;Pavel and Jitka, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, pharmaceutical research and development are very challenging because of high cost, high risk and lengthy research period (Fan et al, 2012). Traditional Chinese medicine (TCM) has attracted much attention owing to its effectiveness against many diseases and proven safety in clinical use over 8000 years (Xie and Leung, 2009;Pavel and Jitka, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…SMZ was selected as the appropriate IS, as it was stable and did not exist in rat blank control plasma. The total analysis time was 9.0 min and the retention time of MH was 7.9 min, which was significantly shorter than that achieved in a previous method, with better resolution (68). …”
Section: Discussionmentioning
confidence: 65%
“…The study utilized normal rats, not CMS rats, in contrast to the present study (14). Another study aimed to identify an antidepressive compound found in TCM by a novel approach known as ethnopharmaco-kinetic- and activity-guided isolation (EAGI) (6). In this study, MH, a compound whose antidepressive effect is similar to FA and CSS, was isolated for the first time from FA (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations